2021
DOI: 10.1109/tpami.2019.2961349
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Fixed-Length Fingerprint Representation

Abstract: We present DeepPrint, a deep network, which learns to extract fixed-length fingerprint representations of only 200 bytes. DeepPrint incorporates fingerprint domain knowledge, including alignment and minutiae detection, into the deep network architecture to maximize the discriminative power of its representation. The compact, DeepPrint representation has several advantages over the prevailing variable length minutiae representation which (i) requires computationally expensive graph matching techniques, (ii) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 53 publications
0
74
0
Order By: Relevance
“…Recently, some novel fingerprint representations demonstrated superior authentication accuracy, which lay a great foundation for the future development of fingerprint template protection methods, for example, the Minutia Cylinder-Code (MCC) [32], a representation based on 3D data structures (called cylinders) and the DeepPrint [33], a fixedlength fingerprint representation of only 200 bytes. Built upon this novel fingerprint representation, we will investigate template protection for fingerprint biometric systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some novel fingerprint representations demonstrated superior authentication accuracy, which lay a great foundation for the future development of fingerprint template protection methods, for example, the Minutia Cylinder-Code (MCC) [32], a representation based on 3D data structures (called cylinders) and the DeepPrint [33], a fixedlength fingerprint representation of only 200 bytes. Built upon this novel fingerprint representation, we will investigate template protection for fingerprint biometric systems.…”
Section: Discussionmentioning
confidence: 99%
“…Scores are computed using both of these representations and then fused together using a sum score fusion for a final similarity score. 1) Texture Representation: To extract our textural representation, we fine-tune the DeepPrint network proposed by Engelsma et al in [28] on a training partition of the publicly available datasets which we aggregated (Table III). We note that we do not include any data from our newly collected ZJU dataset for fine-tuning as we want this dataset to remain completely unseen for a more rigorous evaluation.…”
Section: B Representation Extractionmentioning
confidence: 99%
“…Our approach is more comprehensive than published methods which focus on only a subset of these modules needed for state-of-the-art performance. 2) A fully automated, preprocessing pipeline to map contactless fingerprints into the domain of contact-based fingerprints and a contactless-contact adaptation of Deep-Print [28] for representation extraction. Our preprocessing and representation extraction is generalizable across multiple datasets and contactless capture devices.…”
Section: Introductionmentioning
confidence: 99%
“…Militello et al [42] showed the performance of pre-trained CNNs, including AlexNet [31], GoogLeNet [55], and ResNet [26] for the fingerprint image classification. DeepPrint network [21] learns alignment and minutiae from fingerprint images, making fixed-length fingerprint representations of only 200 bytes. Kai and Anil [5] proposed a CNN to learn an orientation field dictionary for fingerprint alignment.…”
Section: Related Workmentioning
confidence: 99%